Uso de tecnologías de información y comunicación en la atención al usuario de la Municipalidad Provincial de Requena, 2020 - Vásquez Upiachihua, Glinda Ursula (2021)
The general objective of this research was to determine the relationship between information and communication technologies in customer service of the Provincial Municipality of Requena, 2020. Being a quantitative study, correlation level and non-experimental design; which has taken a sample of 324 users from 2655 people; Likewise, the survey technique and the questionnaire have been used as an instrument for data collection, which have been processed in the Excel and SPSS programs. Achieving the conclusion that information and communication technologies are related to customer service; corroborated by a correlation coefficient of 0.650, this being a moderate positive. Operational planning is related to customer service; corroborated by a correlation coefficient of 0.551, this being a moderate positive. Electronic municipal government is related to customer service; corroborated by a correlation coefficient of 0.529, this being a moderate positive. The simplification of procedures is related to customer service; corroborated by a correlation coefficient of 0.550, this being a moderate positive. The benefits of ICT are related to customer service; corroborated by a correlation coefficient of 0.524, this being a moderate positive.